Dynamic contrast-enhanced MRI parameters as biomarkers for the effect of vatalanib in patients with non-small-cell lung cancer. (April 2014) - Nensa, Felix; Stattaus, Jörg; Morgan, Bruno; Horsfield, Mark A; Soria, Jean-Charles; Besse, Benjamin; Gounant, Valerie; Khalil, Antoine; Seng, Katja; Fischer, Berthold; Krissel, Heiko; Laurent, Dirk; et al.
ABSTRACT: : Aims: To assess the utility of dynamic contrast-enhanced MRI parameters in the demonstration of early antiangiogenic effects and as prognostic biomarkers in second-line treatment of advanced-stage non-small-cell lung cancer with vatalanib.Patients & methods: The transfer constant (K trans ) and the initial area under the contrast concentration–time curve at 60 s (AUC60 ) were assessed in 46 patients. Changes were compared with response evaluation from computed tomography imaging and Response Evaluation Criteria In Solid Tumors guidelines.Results: Statistically significant mean reductions in K trans (38.4%; p < 0.0001) and AUC60 (24.9%; p < 0.0001) were found at day 2. After 12 weeks, 16 patients (35%) demonstrated stable disease and 30 (65%) demonstrated progressive disease. No statistically significant differences in day 2 K trans and AUC60 reductions between stable disease and progressive disease patients were found.Conclusion: Dynamic contrast-enhanced MRI can demonstrate a statistically significant reduction in vascular parameters of non-small-cell lung cancer, but does not predict patient outcome.